(untitled) (Circe de clásicos y modernos, 2021)
In this article, I will study some passages of Euripides’ The Trojan Women in search of possible meanings of justice in the text. First, I will analyze the pact made between Poseidon and Athena in the first part of the prologue (1-97); then, I will concentrate on the paradoxical intervention of Cassandra, before being embarked as Agamemnon’s slave (308-461); finally, I will highlight some points of the agón between Hecuba and Helen, which has Menelaus as judge (860-1059). I consider that in these passages there is some allusion to weak conceptions of justice, although I will come to pessimistic conclusions in this regard.